2021
DOI: 10.1021/acsanm.1c01750
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Photocatalytic Anaerobic Oxidation of Benzyl Alcohol over Pt-Loaded Defective SrTiO3 Nanoparticles

Abstract: Photocatalytic selective oxidation of alcohols under mild conditions is an emerging technique to encounter the global challenges of energy source shortages and the green synthesis perspective. Herein, we investigate the solvent effects on heterogeneous photocatalytic anaerobic oxidation of benzyl alcohol with Pt-loaded defective SrTiO 3 nanoparticles. It is found that the optimal solvent is water mixed with a small amount of dimethylformamide (DMF) or acetonitrile, while the solvent effects on the oxidation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Ion doping is considered to be an effective method to improve the photocatalytic property of SrTiO 3 . Common metal ions doped include Pt, Ag, Au, Ru, Pd, Cu, Al, Mn, and so on [7][8][9][10][11][12][13][14]. Mn-doped SrTiO 3 photocatalytic materials can reduce the band gap, while the preparation technology is mature and has been well developed and applied in the field of photocatalysis and widely used in the fields of photocatalytic degradation and photocatalytic water splitting hydrogen production [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ion doping is considered to be an effective method to improve the photocatalytic property of SrTiO 3 . Common metal ions doped include Pt, Ag, Au, Ru, Pd, Cu, Al, Mn, and so on [7][8][9][10][11][12][13][14]. Mn-doped SrTiO 3 photocatalytic materials can reduce the band gap, while the preparation technology is mature and has been well developed and applied in the field of photocatalysis and widely used in the fields of photocatalytic degradation and photocatalytic water splitting hydrogen production [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…, or Cl 2 ), causing serious environmental concerns. 7,8 As a result, photocatalysis has emerged as one of the most energy-efficient and effective green environmental technologies for selective oxidation. Additionally, TiO 2 -based nanomaterials have been experimentally proven to be effective catalysts for accelerating BA conversion and BAD-selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of secondary components such as cocatalysts and heterojunction formation allow the photoreforming selectivity to be tuned to favor the generation of aldehydes or C–C coupling products. Numerous types of photocatalysis have been developed for the highly selective formation of aldehydes, with recent high-efficiency photocatalysts achieving selectivity of ≥90%. The hydrogen generated when photocatalysts are used for benzyl alcohol conversion is also favorable; for example, Hao et al developed nickel-sulfide-decorated zinc sulfide nanorods for the photocatalytic transformation of benzyl alcohol to benzaldehyde coupled with H 2 evolution …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that the oxidative ability of the catalyst is primarily enhanced via the use of cocatalyst systems, which improve transformation efficiency and selectivity. …”
Section: Introductionmentioning
confidence: 99%